Linked and Match Antara Program Studi MICE Politeknik Negeri Jakarta Dengan PT MD Media: Studi Kasus Penilaian Beban Kerja 2024 - Gultom, Hosea David; Judisseno, Rimsky K. (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2025)
Vocational education aims to produce graduates who are ready for work and aligned with industry needs. This study analyzes the 'link and match' between the curriculum of the MICE (Meeting, Incentive, Convention, and Exhibition) Study Program at the Polytechnic Negeri Jakarta (PNJ) and work practices in the event organizer industry, through a case study of workload assessment at PT Metra Digital Media (MD Media). The objective of this research is to evaluate the alignment between theories acquired during lectures and their practical application in the professional world, particularly in event management. This study employed a qualitative method, with data collection techniques including direct observation, interviews, and documentation during a three-month internship period. The analysis results indicate a significant correlation between subjects such as Logistics Management, Site Inspection, Corporate Event, Special Event, and Convention Planning, and the tasks performed at PT MD Media, with an average suitability percentage ranging from 65% to 90%. Nevertheless, the gap analysis revealed that field practice demands more flexible adaptation and the handling of more complex aspects compared to the theoretical frameworks taught. In conclusion, there is a good 'link and match' between the PNJ MICE study program and industry needs, where theoretical knowledge serves as a crucial foundation for professional practice. However, the development of dynamic practical competencies remains necessary to effectively meet industry challenges. Keywords: Link and Match, MICE, Workload Analysis, Event Management, Vocational Education